2011
DOI: 10.1007/s10709-012-9641-1
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive microclimatic evolution of the dehydrin 6 gene in wild barley at “Evolution Canyon”, Israel

Abstract: Dehydrins are one of the major stress-induced gene families, and the expression of dehydrin 6 (Dhn6) is strictly related to drought in barley. In order to investigate how the evolution of the Dhn6 gene is associated with adaptation to environmental changes, we examined 48 genotypes of wild barley, Hordeum spontaneum, from "Evolution Canyon" at Mount Carmel, Israel. The Dhn6 sequences of the 48 genotypes were identified, and a recent insertion of 342 bp at 5'UTR was found in the sequences of 11 genotypes. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Similar results were unfolded in our analysis of Dehydrin 6 (Dhn6) (Yang et al 2012) and small Heat Shock Proteins, sHSP (Zhang et al 2014). Natural microclimatic selection appears to adaptively diversify the duplicated copies of hsp 17 of wild barley between the opposite warmer and cooler slopes, suggesting that the recent duplication of stress-responsive genes was subjected to adaptive evolution.…”
Section: Drought-resistance Dehydrin 1 Adaptationssupporting
confidence: 82%
“…Similar results were unfolded in our analysis of Dehydrin 6 (Dhn6) (Yang et al 2012) and small Heat Shock Proteins, sHSP (Zhang et al 2014). Natural microclimatic selection appears to adaptively diversify the duplicated copies of hsp 17 of wild barley between the opposite warmer and cooler slopes, suggesting that the recent duplication of stress-responsive genes was subjected to adaptive evolution.…”
Section: Drought-resistance Dehydrin 1 Adaptationssupporting
confidence: 82%
“…These results suggested that the operation of natural selection and the adaptive nature of genetic variation could be explained by the variation of ecological factors. The sharp regional gradient of climatic conditions from north to south in Israel, with increasing temperatures and decreasing water availability towards the semiarid zones in southern Israel play a major role as do microecological climatic and edaphic stresses [16,52]. That is also why latitude was found to be associated with frequency variation for most SNP allele (Additional file 3: Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the recent studies of the stress-induced genes Dhn1 (Yang et al, 2009) and Dhn6 (Yang et al, 2011), hsp17 has higher divergences, while the disease resistance-related gene Isa had fewer polymorphisms (Cronin et al, 2007). The ECI model provides clues to future evolutionary studies on both stress genes and speciation genes.…”
Section: Model Of the Eci Is Valuable To Study The Local Gene Adaptationmentioning
confidence: 92%